Clinical and radiological features of Marchiafava–Bignami disease. Issue 5 (February 2018) - Dong, Xiaoyu; Bai, Chaobo; Nao, Jianfei
Abstract : Abstract: Marchiafava–Bignami disease (MBD) is a rare neurological disease usually associated with chronic alcoholism and characterized by demyelination and necrosis. Our aims were to describe the clinicoradiological features and identify factors that may affect the prognosis of patients with MBD. We examined clinical manifestations, laboratory results, and neuroradiological features of 9 patients with MBD. The patients were classified into 2 subgroups (favorable and poor outcome subgroups) based on the Modified Oxford Handicap Scale (MOSH). In addition, we compared the clinical and neuroimaging features between the 2 subgroups. Nine adult male patients (age of onset range 37–62 years, with a mean age of 47.00 ± 14.50 years) were included in this study. According to MOSH, 4 patients were placed in the poor outcome subgroup (MOHS ≥ 3), 5 patients were placed in the favorable outcome subgroup (MOHS ⩽ 2). Relatively high score of MAST-C (≥6) ( P  = .008), extracallosal lesions ( P  = .048), GCS ( P  = .026), cerebral lobe impairment ( P  = .048) was significantly more common in the poor outcome subgroup. Clinical manifestations of MBD are variable and lack specificity. Early diagnosis by relatively specific performance of bisymmetric lesions in corpus callosum of diffusion-weighted imaging (DWI) may affect the prognosis. The prognosis of patients with severe disturbance of consciousness, heavy alcohol consumption, extracallosal lesions, cerebral lobe impairment is probably unfavorable. Abstract : Supplemental Digital Content is available in the text